Thermodynamic investigations on the inclusion complexation of piroxicam with cyclodextrin derivatives - S. Charumanee (2018)
Thermodynamic studies of piroxicam in aqueous solution complexed with β-cyclodextrin (β-CD), γ-cyclodextrin (γ-CD) and two β-cyclodextrin derivatives, hydroxypropyl-β-cyclodextrin (HP-β-CD) and methyl-β-cyclodextrin (Me-β-CD) were performed at different temperatures and pH values using the phase solubility method. The phase solubility diagrams of β-CD, γ-CD and HP-β-CD is of A L-type behavior, indicating the formation of 1:1 complexes. The related stability constants range from β-CD > γ-CD > Me-γ-CD > HP-β-CD, respectively. An A P-type solubility diagram is observed for Me-β-CD, indicating the formation of 1:2 complexes at higher CD concentrations. From the temperature dependence of the equilibrium constants the reaction enthalpies and entropies have been determined. The contributions of the reaction entropies are small and no enthalpy-entropy- compensation is observed, except for γ-CD, where a very small negative reaction entropy could be estimated. Moreover, the influence of the pH value is rather high, because the differently charged forms of piroxicam show different solubility behavior in water. © Österreichische Apotheker- Verlagsgesellschaft m. b. H.